Judicial Preview Sebagai Mekanisme Verifikasi Konstitusionalitas Suatu Rancangan Undang-Undang - Alek Karci Kurniawan (Jurnal Konstitusi, 2014)
The many the petition judicial review of legislation, as legislation product Parliament and the President, at the Constitutional Court, indicates law making     as any of the products of law in Indonesia is currently seen by many parties have  not succeeded meet the expectations ofsociety. Contrasts, with a consequence has hundreds of articles that was canceled by Constitutional Courtsince its establishment it indicates so bad law making over the years.One of its causes weakness in order to scrutinize the drafts of the legislation in accordance with the constitution and people’s expectations. Therefore, in this research wants examine and develop a mechanism to check list to en sure that it each law making process in accordance with the constitution and people’s expectations. In this research, a method use disnormative juridical by using conceptual approach, historical and regulatory. From the research explores an extra mechanism for Constitutional Court to verify the value of constitutionality a draft law.